Optimizing the Growth of Porang Plants (Amorphophalus Muelleri) using a Combination of Market Waste Compost and Growmore Fertilizer - Purnama, Indra; Susi, Neng; Ihsan, Fikratul; Franseda, Franseda (Jurnal Pertanian, 2023)
Porang (Amorphophalus Muelleri) is a tuber plant from Araceae family that is easily live in various types and soil condition. In the food industry porang flour is used as a thickening agent, emulsion stabilizer and gel former, while in the pharmaceutical industry it is used as a coating material. This was do the increased in demand for exports of porang tubers in the form of flour and chips. The increasing demand for porang, so that porang cultivation has economic value. The selection of the appropriate fertilizer is one of the efforts to increase porang productivity. Therfore, the aim of this research was to obtain the scintific data about interaction of organic waste market fertilizerand growmore fertilizer toward of vegetative growth of porang plant. This research used RAL Factorial have 2 factor with 3 treatments level each others were the first factor is doses of organic waste market fertilizer (0g/polybag, 200 g/polybag and 400 g/polybag) and the second factor is doses of growmore fertilizer (0 g/l, 1 g/l and 2 g/l). The parameters in this research were plant height, petiole diameter, number of petioles and number of lateral roots of porang plant. The result on this research showed that interaction of organic waste market fertilizer and growmore fertilizer was signicantly affected of plant height, petiole diameter and number of lateral roots, but did not significantly affected of number of porang petioles. The best treatment obtained from interaction of organic waste market fertilizer at dosage 400g/polybag and growmore fertilizer at a dosage 1g/l.